Lactobacillus rhamnosus GG Modulates Mitochondrial Function and Antioxidant Responses in an Ethanol-Exposed In Vivo Model: Evidence of HIGD2A-Dependent OXPHOS Remodeling in the Liver - Celia Salazar; Marlen Barreto; Alfredo Alfonso Adriasola-Carrasco; Francisca Carvajal; José Manuel Lerma-Cabrera; Lina María Ruiz (Antioxidants, 2025)
The gut microbiota plays a central role in host energy metabolism and the development of metabolic disorders, partly through its influence on mitochondrial function. Probiotic supplementation, particularly with Lactobacillus rhamnosus GG, has been proposed as a strategy to modulate the microbiota and improve host metabolic health. Adolescent binge-like alcohol consumption is a critical public health issue known to induce neuroinflammation, oxidative stress, mitochondrial dysfunction, and intestinal dysbiosis, contributing to disorders such as alcoholic liver disease (ALD). This study aimed to evaluate the effects of L. rhamnosus GG supplementation on mitochondrial physiology in Sprague Dawley rats exposed to binge-like ethanol (BEP group) or saline (SP group) during adolescence (postnatal days 30–43). Starting on postnatal day 44, L. rhamnosus GG was administered orally for 28 days. Fecal colonization was confirmed by qPCR, and mitochondrial function was assessed in the liver, heart, and bone marrow through quantification of NADH, ATP, ADP/ATP ratio, total antioxidant capacity, and the expression of mitochondrial genes Higd2a, MnSOD1, and AMPKα1. L. rhamnosus GG supplementation induced tissue-specific mitochondrial adaptations. In the liver, it increased Higd2a expression and restored antioxidant and energy balance in ethanol-exposed rats. In the bone marrow, it reversed ethanol-induced metabolic stress and enhanced AMPKα1 expression. In contrast, in the heart, L. rhamnosus GG had minimal impact on mitochondrial energy markers but increased antioxidant capacity, indicating a more limited, redox-focused effect. These findings suggest that L. rhamnosus GG exerts context-dependent, tissue-specific benefits on mitochondrial physiology, primarily through the modulation of antioxidant defenses, activation of AMPKα1, and remodeling of respiratory complexes. This probiotic may represent a promising therapeutic strategy to mitigate mitochondrial dysfunction associated with early-life alcohol exposure.